Against the tide - Farah Iqbal (2008)
ACCOMPANIED BY: VIDEO (VCD) – PLEASE APPROACH ACRC LOAN COUNTER. The project takes the form of a 30-minute video documentary that revolves around an old retired schoolteacher living in a fishing village in the southern islands of Laos. In our documentary, the schoolteacher’s passion for fishing shines through amidst the ongoing tourist development of his village, which presents a contrasting image of economic survival.